Phenomenology and Theology: Situating Heidegger’s Philosophy of Religion - Russell, Matheson (Sophia, 2011)
This essay considers the philosophical and theological significance of the phenomenological analysis of Christian faith offered by the early Heidegger. It shows, first, that Heidegger poses a radical and controversial challenge to philosophers by calling them to do without God in an unfettered pursuit of the question of being (through his ‘destruction of onto-theology’); and, second, that this exclusion nonetheless leaves room for a form of philosophical reflection upon the nature of faith and discourse concerning God, namely for a philosophy of religion in a phenomenological mode (as exemplified most clearly in Heidegger’s 1920/21 lectures on the phenomenology of religious life). However, it is argued that the theological roots of Heidegger’s own phenomenological analyses subvert his frequently asserted claim concerning the incompatibility of Christian faith and philosophical inquiry.